A companion of Dragomir’s generalization of the Ostrowski inequality and applications to numerical integration - Alomari, M.W. (Український математичний журнал, 2012)
Some analogs of Dragomir’s generalization of the Ostrowski integral inequality are established. Some sharp inequalities are proved. An application to the composite quadrature rule is provided. Встановлено аналоги узагальнення Драгомiра iнтегральної нерiвностi Островського, отримано деякi точнi нерiвностi. Наведено застосування до складеної квадратурної формули.